ASSOCIATIVE MEANING AND SOCIAL REPRESENTATIVE OF TOP 20 POP MUSIC 2022 IN THE WORLD: ANALYSIS OF BILLBOARD POP MUSIC END-YEAR CHART 100 - Nelly Efviana; Evi Jovita Putri (IKIP Siliwangi, 2023)
In the context of globalization, which brings profound cultural and social changes to society, language undergoes significant impacts, exemplified by the addition of approximately 600 thousand words to the Oxford English Dictionary. These additions encompass various slang terminologies commonly used in popular culture during this era. Popular culture, produced for mainstream audiences, encompasses various forms of entertainment, with 'pop music' as a significant expression. This research explores associative meanings and social representations in popular music lyrics using Leech's theory for meaning and Taine's Sociology of Literature theory for social context. Findings reveal diverse meanings in the lyrics, such as connotative, reflected, affective, collocative, and social meanings, reflecting themes like drug use, sexual activity, gender, sexuality, and women's empowerment. Prominently, connotative, reflected, and social meanings emerge as the most prevalent, with sexual activity being the most frequently depicted social theme in the data. This research sheds light on how popular culture music serves as a powerful medium for expressing and reflecting the various social phenomena and transformations occurring during the contemporary globalized era.